Systematic Determination of Replication Activity Type Highlights Interconnections between Replication, Chromatin Structure and Nuclear Localization - Farkash-Amar, Shlomit; David, Yaara; Polten, Andreas; Hezroni, Hadas; Eldar, Yonina C.; Meshorer, Eran; Yakhini, Zohar; Simon, Itamar (PLOS ONE, 2012)
DNA replication is a highly regulated process, with each genomic locus replicating at a distinct time of replication (ToR). Advances in ToR measurement technology enabled several genome-wide profiling studies that revealed tight associations between ToR and general genomic features and a remarkable ToR conservation in mammals. Genome wide studies further showed that at the hundreds kb-to-megabase scale the genome can be divided into constant ToR regions (CTRs) in which the replication process propagates at a faster pace due to the activation of multiple origins and temporal transition regions (TTRs) in which the replication process propagates at a slower pace. We developed a computational tool that assigns a ToR to every measured locus and determines its replication activity type (CTR versus TTR). Our algorithm, ARTO (Analysis of Replication Timing and Organization), uses signal processing methods to fit a constant piece-wise linear curve to the measured raw data. We tested our algorithm and provide performance and usability results. A Matlab implementation of ARTO is available at http://bioinfo.cs.technion.ac.il/people/zohar/ARTO/. Applying our algorithm to ToR data measured in multiple mouse and human samples allowed precise genome-wide ToR determination and replication activity type characterization. Analysis of the results highlighted the plasticity of the replication program. For example, we observed significant ToR differences in 10–25% of the genome when comparing different tissue types. Our analyses also provide evidence for activity type differences in up to 30% of the probes. Integration of the ToR data with multiple aspects of chromosome organization characteristics suggests that ToR plays a role in shaping the regional chromatin structure. Namely, repressive chromatin marks, are associated with late ToR both in TTRs and CTRs. Finally, characterization of the differences between TTRs and CTRs, with matching ToR, revealed that TTRs are associated with compact chromatin and are located significantly closer to the nuclear envelope. Supplementary material is available. Raw and processed data were deposited in Geo (GSE17236).